Ferroelectric properties in metal-coordinated complex tris(2-hydroxyethyl) ammonium trichloro cadmium(ii). Issue 6 (25th January 2022) - Tang, Zheng; Sun, Xiao-Fan; Gao, Zhang-Ran; Li, Dong; Jiao, Shu-Lin; Xu, Cui-Ping; Tang, Wen-Chao; Yang, Zhu; Chen, Peng; Xu, Yan-Ming; Xu, Jinlong; Cai, Hong-Ling; et al.
Abstract : The λ -shape dielectric anomaly follows the Curie–Weiss law with a 105.8-fold change at a frequency of 500 Hz. The spontaneous polarization of TATC can reach 1.4 μC cm −2 . The TATC crystal has a 4.03 eV indirect bandgap. Abstract : The metal-coordinated complex tris(2-hydroxyethyl)ammonium trichloro cadmium(ii ) (TATC ) with a space group of P 21 / c at room temperature was obtained in aqueous solution. A paraelectric–ferroelectric phase transition (from the monoclinic P 21 / c phase to the monoclinic P 21 phase) occurs at a temperature of 270 K/247 K in the heating/cooling process, which belongs to the order–disorder type transition, and is consistent with the thermodynamic analysis from DSC results. The λ-shape dielectric anomaly follows the Curie–Weiss law with a 105.8-fold change at a frequency of 500 Hz. The maximum value of the pyroelectric coefficient P e is about 0.11 μC cm −2 K −1, which is higher than the classical ferroelectric crystal TGS (5.5 × 10 −2 μC cm −2 K −1 ). The maximum value of the related figures of merit (FOMs) M 1 and M 2 at a frequency of 1 MHz is 0.0108 cm 2 μC −1 and 0.0245 cm 3/2 J −1/2, respectively, which is higher than that of TGS (4 × 10 −3 cm 2 μC −1 and 0.01 cm 3/2 J −1/2 ). The compensation method (the Sawyer–Tower method) and the double-wave method were used to obtain ferroelectric hysteresis loops and display the ferroelectricity of TATC . The spontaneous polarization and the coercive field of TATC can reach about 1.4 μC cm −2 and 0.3 kV cm −1, respectively. The intense dielectric anomaly and the near-room-temperature T c value indicate that TATC can be an applicable dielectric switching material.